(untitled) (Nonconventional Technologies Review, 2024)
Main elements of the analytical modelling are presented for the laser cutting process. Analytical models consider the physical phenomena that occur and formulate balance equations. In current approaches, analytical modelling is integrated into simulation using software dedicated to this purpose. This moves away from the formation and knowledge of elementary models. The technological applicability of analytical modelling is reduced compared to the empirical one, through correlation formulas, because the analytical model is either too general or too particular. The sequential treatment of a complex processing process and the modelling of physical phenomena that have a significant contribution can be a way to exploit analytical modelling.